First Annotated Genome of a Mandibulate Moth, Neomicropteryx cornuta, Generated Using PacBio HiFi Sequencing. (1st October 2021) - Li, Xuankun; Ellis, Emily; Plotkin, David; Imada, Yume; Yago, Masaya; Heckenhauer, Jacqueline; Cleland, Timothy P; Dikow, Rebecca B; Dikow, Torsten; Storer, Caroline G; Kawahara, Akito Y; Frandsen, Paul B
Abstract: We provide a new, annotated genome assembly of Neomicropteryx cornuta, a species of the so-called mandibulate archaic moths (Lepidoptera: Micropterigidae). These moths belong to a lineage that is thought to have split from all other Lepidoptera more than 300 Ma and are consequently vital to understanding the early evolution of superorder Amphiesmenoptera, which contains the order Lepidoptera (butterflies and moths) and its sister order Trichoptera (caddisflies). Using PacBio HiFi sequencing reads, we assembled a highly contiguous genome with a contig N50 of nearly 17 Mb. The assembled genome length of 541, 115, 538 bp is about half the length of the largest published Amphiesmenoptera genome ( Limnephilus lunatus, Trichoptera) and double the length of the smallest ( Papilio polytes, Lepidoptera). We find high recovery of universal single copy orthologs with 98.1% of BUSCO genes present and provide a genome annotation of 15, 643 genes aided by resolved isoforms from PacBio IsoSeq data. This high-quality genome assembly provides an important resource for studying ecological and evolutionary transitions in the early evolution of Amphiesmenoptera.